Speleothem Laminae Counting and Growth Rate - Corey Wilson (Undergraduate Journal of Mathematical Modeling: One + Two, 2012)
The goal of this project is to determine if there is a correlation between annual laminae in speleothems and Uranium dating. To do this, we counted laminae using high-resolution images and calculated a line of the best fit for the resulting data. We found that our data could supplement Uranium dating, but unless more data is obtained, laminae counting gives relatively imprecise age and growth rate estimates.